One-dimensional self-weight consolidation with continuous drainage boundary conditions : solution and application to clay-drain reclamation - Feng, Jianxue (2021)
Traditional consolidation theories cannot provide good predictions of consolidation settlement in land reclamation because of their assumptions that the influence of soil's self-weight is often neglected, and the drainage boundary is considered as fully pervious/impervious. In view of these limitations, an analytical solution is derived for one-dimensional self-weight consolidation problems with a continuous drainage boundary using the finite Fourier sine transform method. Following the classical Terzaghi's small strain theory, the soil's self-weight is considered to produce consolidation settlement in dredged materials with a constant coefficient of consolidation. The continuous drainage boundary can essentially describe the time-dependent variation of drainage capacity at the interface between two adjacent soil layers. By reducing the interface parameters, the effectiveness of the calculation is demonstrated against the Terzaghi's solution. The influence of interface parameters and soil's self-weight stress coefficient on self-weight consolidation is discussed. As expected, the rate of consolidation considering the self-weight stress is faster, although the dependency of consolidation rate on the material property of void ratio is neglected. Moreover, the plane of maximum excess pore-water pressure is estimated as a function of time factor, based on which a design chart is developed to optimize the layout of horizontal drains in land reclamation.